Corporate Governance Reforms in the EU : Do They Matter and How? - Ivaschenko, Iryna; Koeva Brooks, Petya (Washington, D.C. : International Monetary Fund, 2008)
This paper proposes a new approach to quantifying the effects of corporate governance reforms, by focusing on the dynamics of the voting premiums, a measure of the private benefits of control in a corporation. The results indicate that the reforms have been successful in reducing the voting premiums EU-wide. Moreover, more intense and broad reform efforts (such as introducing national reforms beyond and above the EU-wide initiatives) bring higher and longer lasting benefits. Our findings also suggest that the market for corporate control in Europe has become more integrated, as illustrated by the lower dispersion in voting premiums across countries and over time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet